Evaluation of an E-Learning System for Physical Education - Zhao, P.; Dong, Y; Ji, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction This paper describes changes in the the status quo in relation to E-Learning in physical education (P.E.) and health classes, and which is designed to provide a good environment for students` self-learning and co-learning, as well as broadening of the teachers` teaching information resources. Methods Methods of consulting relevant sources of literature, and processes involved in establishing the structure and function of an online learning system and essential technology are described in this paper. The on-line learning system is based on B/S structure, ASP entire station construction technology, and Author Ware which is based on flow graphical representation. Results / Discussion Development of the "Sports and Health" online education system was based on the B/S structure and ASP technology. The system developed has 7 subsystems: 1. Network curriculum; 2. Fashion movement; 3. Online test; 4. Downloading center 5. Picture center; and 6. HEU BBS 7. News center. In developing the pedagogy system, the multimedia classroom and network self-learning systems were used with attention paid to the connection of multimedia teaching and learning, and a proposed sports cooperation learning method. The project established the school`s multimedia online system primarily, based on B/S and the Client composite structure, adopting the ASP dynamic homepage technology and constructing an online learning network (http://sports.hrbeu.edu.cn), with IIS5.0 being the server software. The equipment mainly comprises computers, touch screen computers, digital video and audio devices. The software system is applied to user management, video and audio ordering programs, collection and production of course materials, a courseware order program, database management and store management. It may also be used to establish teaching practices.. With the development of network technology, the system is designed to provide constant feedback and information filtration functions. The system also allows for individualised programming for students.